Singing one`s image: slavic national and state anthems as realms of memory or ‘blemishes’ on the face of history (Colloquia Comparativa Litterarum, 2019)
This essay presents a chronological and typological overview of the Slavic national and state anthems through the lens of Pierre Nora’s notion of “realms of memory”. A special focus is placed on the common practice of appropriating foreign and older national anthems and transforming them into new hymns. The Slavic state anthems are classified into three groups: anthems that have gradually become lasting realms of national memory, anthems that have the potential to become national realms of memory, and anthems that have failed to achieve a status of a realm of memory. Among the latter are the state anthems, created specifically for the needs of some of the totalitarian regimes in the Soviet block that are viewed today as ‘blemishes’ on the face of national history.
Keywords: National and State Anthem(s); realms of memory; Slavs